Premating barriers in young sympatric snail species - Maltseva, Arina L. (Sci Rep, 2021)
Sympatric coexistence of recently diverged species raises the question of barriers restricting the gene flow between them. Reproductive isolation may be implemented at several levels, and the weakening of some, e.g. premating, barriers may require the strengthening of the others, e.g. postcopulatory ones. We analysed mating patterns and shell size of mates in recently diverged closely related species of the subgenus Littorina Neritrema (Littorinidae, Caenogastropoda) in order to assess the role of premating reproductive barriers between them. We compared mating frequencies observed in the wild with those expected based on relative densities using partial canonical correspondence analysis. We introduced the fidelity index (FI) to estimate the relative accuracy of mating with conspecific females and precopulatory isolation index (I(PC)) to characterize the strength of premating barriers. The species under study, with the exception of L. arcana, clearly demonstrated preferential mating with conspecifics. According to FI and I(PC), L. fabalis and L. compressa appeared reliably isolated from their closest relatives within Neritrema. Individuals of these two species tend to be smaller than those of the others, highlighting the importance of shell size changes in gastropod species divergence. L. arcana males were often found in pairs with L. saxatilis females, and no interspecific size differences were revealed in this sibling species pair. We discuss the lack of discriminative mate choice in the sympatric populations of L. arcana and L. saxatilis, and possible additional mechanisms restricting gene flow between them.